2013
DOI: 10.1017/s0963548313000357
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Number ofk-Cliques in Graphs with Bounded Independence Number

Abstract: Erdős asked in 1962 about the value of f (n, k, l), the minimum number of k-cliques in a graph with order n and independence number less than l. The case (k, l) = (3, 3) was solved by Lorden. Here we solve the problem (for all large n) for (3, l) with 4 ≤ l ≤ 7 and (k, 3) with 4 ≤ k ≤ 7. Independently, Das, Huang, Ma, Naves, and Sudakov resolved the cases (k, l) = (3, 4) and (4, 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 23 publications
(75 reference statements)
0
44
0
Order By: Relevance
“…We note that it is an old and intriguing problem how small p(K k , G) can be for a large k-clique-free graph. See [4] and the recent work [14]. (8) What are the possible values of t k (T ), given the value of t l (T )?…”
Section: Further Directions and Discussionmentioning
confidence: 99%
“…We note that it is an old and intriguing problem how small p(K k , G) can be for a large k-clique-free graph. See [4] and the recent work [14]. (8) What are the possible values of t k (T ), given the value of t l (T )?…”
Section: Further Directions and Discussionmentioning
confidence: 99%
“…Using the flag algebra semidefinite method, we were able to obtain the bound truerightφHom+(scriptA0,R),φ(W4)0.157516,subject to floating point rounding errors. This suggests that the conjecture is true and that there may be a straightforward (but numerically intensive) proof using the semidefinite method and rounding techniques (see for some examples).…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
“…Using the flag algebra semidefinite method, we were able to obtain the bound ∀ ∈ Hom + ( 0 , ℝ), ( 4 ) ⩽ 0.157516, subject to floating point rounding errors. This suggests that the conjecture is true and that there may be a straightforward (but numerically intensive) proof using the semidefinite method and rounding techniques (see [1,10,11,14,22] for some examples). The intuition of the recursive construction of , is that at every step we have one part −1 ⧵ that maximizes the density of ⃗ 3 (hence is almost balanced) and another part whose vertices all beat the first part.…”
Section: F I G U R Ementioning
confidence: 99%
“…We showed that if the density of independent sets of size r is fixed, the maximum density of s-cliques is achieved when the graph itself is either a clique on a subset of the vertices, or a complement of a clique. On the other hand, the problem of minimizing the clique density seems much harder and has quite different extremal graphs for various values of r and s (at least when α = 0, see [3,13]). Question 7.1.…”
Section: Discussionmentioning
confidence: 99%
“…This is a fifty-year-old question of Erdős, which is still widely open. Das et al [3], and independently Pikhurko [13], solved this problem for certain values of r and s. It would be interesting if one could describe how the extremal graph changes as α goes from 0 to 1 in these cases. As mentioned in the introduction, the problem of minimizing d(K s ; G) in graphs with fixed density of r-cliques for r < s is also open and so far solved only when r = 2.…”
Section: Discussionmentioning
confidence: 99%